Identification of Aquifer Potential in Darungan Village Jember Using Resistivity Vertical Electrical Sounding Method - Zannah, Hildatul; Trapsilo Prihandono; Firdha Kusuma Ayu Anggareni (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2025)
The people of Darungan Village, Jember, feel the water crisis during the dry season. This research aims to detect aquifer potential in Darungan Village using geoelectric method. This research uses geoelectric method with Vertical Electrical Sounding (VES) technique. The data were processed with IPI2WIN and Rockworks software to produce a 3D cross-sectional model and lithology interpretation. The lithology in the study area consists of andesite, sandstone, silt, claystone, sand, tuff, and pyrite. Potential aquifers with resistivity of 0.5 - 23.24 Ωm are present in all lines, with the best potential located in line 2 (sand, 28.21 meters, 2.119 Ωm, 1.128 meters). Further research is needed to map the aquifer in detail and assess its water quality.